The United States Science Curriculum Case Study - Jacobson, Willard ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
In this paper, the status and structure of science education in the United States are reviewed and summarized in six major sections. These include: (1) an introduction (placing science education in the context of the school system as a whole and noting the government's role, administration and funding, school types, external examination policies, national plans, and pressures for reform); (2) aims and objectives of science education (identifying four categories of goals); (3) curriculum development and content (examining patterns found in science curriculum programs); (4) teacher education (reviewing the status of pre-service, pre-service science, and in-service science education); (5) science teaching (reporting on current teaching patterns, teaching methods, student assessment systems, supervisory practices, and professional science associations); and (6) other topics (describing the status of and/or practices related to laboratory facilities, equipment and materials, talented students, special groups, computers, and out-of-school science opportunities). Thirty-four footnotes are appended. (ML)
ERIC Note: Paper presented at the United States-Japan Seminar on Science Education (Honolulu, HI, September 14-20, 1986). Shaded graph on page 5 may not reproduce clearly.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary School Science; Elementary Secondary Education; Government School Relationship; Inservice Teacher Education; Preservice Teacher Education; Science Curriculum; Science Education; Science Instruction; Science Teachers; Secondary School Science; Teacher Education; Teaching Methods; Reports, Descriptive